Squamous Cell Carcinoma Cervical Uterine Metastasis in Abdominal Wall: A Rare Case Report - Cahyono, Endy; Iskandar, Teuku Mirza; Ambari, Ediwibowo; Eka Putra, Very Great; Lubena, Lubena; Wijaya, Dibyo Mukti (Journal of Biomedicine and Translational Research, 2024)
ABSTRACTBackground: About 80% of cervical cancers are squamous cell carcinomas. After severe surgery for squamous cervical cancer, abdominal metastasis is an uncommon occurrence.Case Presentation: A 33-year-old lady was diagnosed with cervical cancer and had a radical hysterectomy, bilateral salpingo-oophorectomy, and bilateral pelvic lymphadenectomy. The histopathological examination showed non-keratinizing squamous cell carcinoma moderately differentiated. A 6 cm suggestive metastatic mass from abdominal region came up three months later after the surgery. An abdominal wall reconstruction surgery was conducted as the treatment for the metastasis mass.Conclusion: The best course of treatment for cervical cancer is still unknown due to the rarity of abdominal metastases. Depending on the severity of the illness and the existence of metastases, each patient receives a unique course of treatment.Keywords: squamous cell carcinoma, hysterectomy, cervical malignancies